(3bhGYO GdTgjOs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3eMeO MSf Hf TjN Ydjs)
(3ChdgG (B:s
(3Gddge Efj CMeOc (B...(3bGYOI Gdabg dZI Gdage hTQYG GdYde HGdCMcGe GdTQYjI GdaQYjI Yf COdJgG GdJaUjdjI aNQL GdYde HGdPhGJ hGdYde HGdCMcGe GdYbdjI hYde CUhd Gdabg hYde GdebdO (B..s
(3BNQgG (B:s
.. (3Ch YOe GdYde HJYdb GdJcdja HPdc Gdjhe Ch YOe MUhd TQW GdceGd YfO WdhY aLQg Ke EPG hbYJ eDGKQI aj UMI GdUhe GSJaGO KhGHg HCLeYg ShGA aYdgG HYO (B...s
(3Yf fSNI HNW GHf GdeDda (B- (3aj ChdgG agQSJ ehVhYGJ jdjg ebOeI aj VHW eSGFd GdcJGH HGSe (B( (3PNjQI jhe GdhYjO aj VHW bhGYO GdTgjO HNW eZGjQ dNW GdfSNI deLghd (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\ 109s
(3GdPQjYI (B17\1029s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis